(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
A field experiment was conducted to evaluate the effects of textile effluent and chemical fertilizer on growth and yield of tossa jute (O-795). The experiment was conducted in a randomized complete block design (RCBD) replicated thrice with six treatments. Growth parameters, viz. plant height, base diameter, green weight, dry matter weight, fiber yield and stick yield were assessed. The highest height (3.7 m), maximum base diameter (16.17 mm), maximum green plants yield with leaves (58.65 t ha-1), maximum green plants yield without leaves (37.46 t ha-1), highest fiber yield (2.87 t ha-1 ) and highest stick yield (6.2 t ha-1) were recorded with T2(100% RDF + 0% effluent). From the economic analysis point of view, it was found that T4 (50% RDF + 50% effluent) showed higher BCR (2.73) than T2 (100% RDF + 0% effluent). Although the best growth performance was observed in T2 (100% RDF + 0% effluent), but in terms of BCR T4 (50% RDF + 50% effluent) was the best. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(1): 15-22